PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP PEMAHAMAN KONSEP IPS SD - Ramadhani, M. Ihsan (Jurnal Pena Karakter (Jurnal Pendidikan Anak dan Karakter), 2019)
Abstract: This study aims to determine the differences in the influence of the make a match learning model compared with expository learning models on the understanding of students' social science concepts. This research uses quasi-experimental research with pretest - posttest control group design. The subjects in this study were students at Tanggul Rejo 2 Public Elementary School in Marabahan District, consisting of class V A totaling 20 students as experimental class and 22 students of class V B as control class in semester II of the academic year 2017/2018. The selection of the experimental class and the control class based on the characteristics of students that are almost the same, by random method. The random results of class V A were selected as the experimental class using the make a match learning model and class V B as the control class using the expository learning model. The data analysis technique used independent sample t-test and paired sample t-test with the help of SPSS 23 for Windows. The results showed that the make a match learning model had a more significant effect than the expository learning model on the understanding of the social studies concept of students in SDN Tanggul Rejo 2 with a significance value of 0,000 <0.05.    Abstrak : Penelitian ini bertujuan untuk mengetahui perbedaan pengaruh model pembelajaran make a match dibandingkan dengan model pembelajaran ekspositori terhadap pemahaman konsep IPS peserta didik. Penelitian ini menggunakan eksperimen semu (quasi-eksperimental research) dengan desain pretest ? posttest control group design. Subyek dalam penelitian ini adalah peserta didik SDN Tanggul Rejo 2 Kabupaten Marabahan, terdiri dari kelas V A berjumlah 20 peserta didik sebagai kelas eksperimen dan 22 peserta didik kelas V B sebagai kelas kontrol pada semester II tahun ajaran 2017/2018. Pemilihan kelas eksperimen dan kelas kontrol berdasarkan karakteristik peserta didik yang hampir sama, dengan cara random. Hasil random terpilih kelas V A sebagai kelas eksperimen menggunakan model pembelajaran make a match dan kelas V B sebagai kelas kontrol menggunakan model pembelajaran ekspositori. Teknik analisis data menggunakan uji independent sample t-test dan paired sample t-test dengan bantuan program SPSS 23 for Windows. Hasil penelitian menunjukkan bahwa model pembelajaran make a match berpengaruh lebih signifikan dibandingkan model pembelajaran ekspositori terhadap pemahaman konsep IPS peserta didik di SDN Tanggul Rejo 2 dengan nilai signifikansi sebesar 0,000 < 0,05.